Összeegyeztethető-e a köztársasági államforma a történeti alkotmánnyal? : Csekey István előadása a Magyar Köztársaság alkotmányáról - Schweitzer, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
István Csekey’s (1889–1963) lecture on the Constitution of the Republic of Hungary (1947) has survived as a manuscript. The internationally renowned representative of 20th century Hungarian public law, besides presenting the basic republican institutions of public law, pointed out that there was not (yet) a radical break in all areas compared to the constitutional conception of the past period. In the area of formalities, there is a certain consistency between the past and the present, which makes even the republican form of government compatible with the construction of the historical constitution. This manuscript is presented in this paper, following a summative assessment of Csekey's academic work.